Implementasi Program Desa Berdaya Melalui Budidaya Maggot Di Kabupaten Mojokerto - Mifta, Dwi Mifta'ul Tesya; Tukiman (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2024)
The increase in the amount of waste has become a serious problem, where it has an impact on several aspects of life, for example air and environmental pollution. Maggot cultivation is the most suitable solution for sustainable waste management and has the capability and appropriate solution for converting organic waste such as fruit, vegetables, animal waste and household waste which can reduce the burden on landfills and has economic value. Researchers applied this type of qualitative research with the aim of obtaining information in the form of descriptions or in-depth and comprehensive explanations regarding the Implementation of the Empowered Village Program through Maggot Cultivation in Sidoharjo Village, Gedeg District, Mojokerto Regency. There are several data collection methods through documentation, field notes and interviews. Then, the data is analyzed through the process of data collection, data presentation, data compression and verification or drawing conclusions which will be applied as qualitative data analysis. These findings show that the implementation of the Empowered Village Program through Maggot Cultivation in Sidoharjo Village has been running effectively and strengthening the village economy. The focus of implementing this program is centered on policy and environmental aspects. The policy aspect includes six points, such as interests affected, types of benefits, desired level of change, decision-making structure, program implementers, and resource allocation, all of which play an important role in the implementation process. Meanwhile, the implementation environment includes the interests, power, strategies of existing actors, criteria of institutions and leaders, as well as obedience and responsiveness, all of which are key factors in the successful implementation of the program.